A BUSINESS PROCESS REENGINEERING AT MULYOAGUNG VILLAGE COMMUNITY SERVICE OFFICE - Ahmad Raihan Djamarullah; Budiman Hamsyurah; Ilyas Nuryasin (IJNMT (International Journal of New Media Technology), 2023)
The Mulyoagung Village Office is a community service office in Mulyoagung Village. One of the services offered at the Mulyoagung village office is a system for making ID cards at the village office using the SiPeduli Desa website, but after analyzing the percentage of throughput efficiency obtained is still 30.85%. There are several processes that require a long waiting time and also manual processing processes so that this condition is still less efficient. Therefore, changes in business processes need to be made to improve the old system that is currently running into a more optimal system. This significant change in business processes is called Business Process Reengineering. The concept of reengineering was born to solve the shortcomings of the old system or legacy system in a business process. Completion of a business process with Business Process Reengineering is done by eliminating processes that do not provide added value and changing manual processes into automated processes by utilizing information technology. The results of this study are business process designs that increase throughput efficiency from 30.85% in the previous process to 89.61% in processes that have been carried out by Business Process Reengineering. The application of Business Process Reengineering can help provide the design of a new business recommendation model that is obtained after an analysis of old business processes and analysis of redesign alternatives is carried out. Business Process Reengineering is also able to improve old processes both in terms of service and speed.